2016
DOI: 10.1515/revneuro-2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation strategies in trauma-related disorders: pathways linking neurobiology and clinical manifestations

Abstract: AbstractEmotion regulation impairments with traumatic origins have mainly been studied from posttraumatic stress disorder (PTSD) models by studying cases of adult onset and single-incident trauma exposure. The effects of adverse traumatic experiences, however, go beyond the PTSD. Different authors have proposed that PTSD, borderline personality, dissociative, conversive and somatoform disorders constitute a full spectrum of trauma-related conditions. Therefore, a comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 110 publications
0
5
0
2
Order By: Relevance
“…Of interest, previous research has also found that dysfunctional (insecure/anxious) adult attachment mediated the relationship between childhood maltreatment and eating disorders (Tasca et al, 2013), somatization (Waldinger et al, 2006), post-traumatic stress symptomatology (Muller et al, 2000) or psychotic disorders (van Dam et al, 2014). In fact, these mental disorders are very common among patients with BPD and raise the question regarding the presence of a potential spectrum of mental disorders related to trauma and attachment disturbances that warrants further investigation (Del Río-Casanova, González, Páramo, Van Dijke, & Brenlla, 2016). If so, BPD and these Axis I mental disorders could represent different phenotypic clinical expressions of the same underlying pathological process.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, previous research has also found that dysfunctional (insecure/anxious) adult attachment mediated the relationship between childhood maltreatment and eating disorders (Tasca et al, 2013), somatization (Waldinger et al, 2006), post-traumatic stress symptomatology (Muller et al, 2000) or psychotic disorders (van Dam et al, 2014). In fact, these mental disorders are very common among patients with BPD and raise the question regarding the presence of a potential spectrum of mental disorders related to trauma and attachment disturbances that warrants further investigation (Del Río-Casanova, González, Páramo, Van Dijke, & Brenlla, 2016). If so, BPD and these Axis I mental disorders could represent different phenotypic clinical expressions of the same underlying pathological process.…”
Section: Discussionmentioning
confidence: 99%
“…This means that increased neuronal activity in ventral regions signals to the dorsal regions to improve neuronal functioning, thus moderating the excitatory affective response of the respective ventral regions (e.g. Bogdan et al, 2015;Del Río-Casanova et al, 2016;Phillips et al, 2008). The increased dorsal and ventral activity suggests that the use of functional strategies of emotion regulation requires greater volitional executive control (dorsal) rather than a preponderant automatic affective response (ventral).…”
Section: Differential Activation Of Brain Network Involved In Emotional Regulation During Recoverymentioning
confidence: 99%
“…Az akut stresszhelyzetben működő predomináns adaptációs válaszmintázat előrevetíti, hogy poszttraumás állapotban (PTSD) milyen típusú tünetek várhatók: hiperarousal vagy inkább disszociatív jellegűek. Krónikus traumatizációnál a traumatizáción alapuló későbbi diagnózis szintén összefüggésbe hozható az érzelemszabályozás sajátosságaival (Del RíoCasanova, González, Páramo, Van Dijke, & Brenlla, 2016).…”
Section: Válaszmintázatok a Stresszre éS Az éRzelemszabályozás Zavaraiunclassified